2006
DOI: 10.1086/504871
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Pneumonia, HIV Therapy, and Disease Progression among HIV‐Infected Women in the HIV Epidemiologic Research (HER) Study

Abstract: High rates of bacterial pneumonia persist among HIV-infected women. Although HAART and TMP-SMX treatment decreased the risk, bacterial pneumonia was associated with an accelerated progression to death. Interventions that improve HAART utilization and promote smoking cessation among HIV-infected women are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
130
2
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(149 citation statements)
references
References 39 publications
9
130
2
7
Order By: Relevance
“…Antiretroviral regimens contain an HIV protease inhibitor and the use of trimethoprim-sulfamethoxazole as prophylaxis for Pneumocystis jiroveci pneumonia may be associated with decreased risk for bacterial pneumonia (Kohli et al, 2006). However, community-acquired pneumonia represents a frequent cause of morbidity and is associated with an increased mortality in HIV-infected patients also in the ART era.…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…Antiretroviral regimens contain an HIV protease inhibitor and the use of trimethoprim-sulfamethoxazole as prophylaxis for Pneumocystis jiroveci pneumonia may be associated with decreased risk for bacterial pneumonia (Kohli et al, 2006). However, community-acquired pneumonia represents a frequent cause of morbidity and is associated with an increased mortality in HIV-infected patients also in the ART era.…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…In a prospective multi-center observational cohort study of HIVinfected women in the United States, Kohli and colleagues report an incidence of bacterial pneumonia of 8.5 cases per 100 person-years in HIV-infected women compared to 0.7 cases per 100 person-years in HIV-negative controls with a history of injection drug use (IDU) or high risk sexual behavior [1]*. Use of ART and trimethoprim-sulfamethoxazole (TMP-SMX) were associated with decreased risk, while lower baseline CD4 count and active cigarette use were associated with increased risk of bacterial pneumonia.…”
Section: Incidencementioning
confidence: 99%
“…1,2 Its incidence has decreased after the introduction of highly active antiretroviral therapy (HAART); 3,4 however, these patients still have a higher risk of acquiring this type of infection, when compared to the general population, 3 in addition to having higher rates of invasive pneumococcal disease 5 and mortality. 6,7 The etiology of community-acquired pneumonia (CAP) in HIV-infected patients is similar to that of immunocompetent patients, with the main agent being Streptococcus pneumoniae.…”
Section: Introductionmentioning
confidence: 99%
“…Infections by Gram-negative bacteria (including Haemophilus influenzae, Pseudomonas aeruginosa and Legionella pneumophila, among others) are common, as well as by Staphylococcus aureus. 1,2,3,6 The following are considered risk factors for CAP in HIV-infected patients: low socioeconomic level, smoking, alcohol consumption, use of intravenous (IV) drugs, comorbidities (including cardiovascular disease, kidney disease or liver cirrhosis), malnutrition, low CD4+ T-cell counts (CD4 < 200 cells/µL), HIV replication and lack of HAART. 2 Regarding prevention, the role of the antipneumococcal vaccine in HIV-infected patients is yet to be defined, as the studies have shown controversial results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation